Bahasa Tabu dalam Masyarakat Gayo Di Kabupaten Bener Meriah - Silfita Yani; Rajab Bahry; Ramli Ramli (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This research is entitled "Tabu Language in the Gayo Society in Bener Meriah Regency". The problem in this research is what taboo words are seen from the help and context when speaking in the Gayo community in Bener Meriah Regency. The research objective is to describe what is taboo language in the Gayo community in Bener Meriah Regency. The source of research data is the Gayo-speaking community appointed as informants. The data collection technique taken is the technique of referring skillfully to record and record while the data analysis technique is done by grouping data into categories of taboo language classification and then found the number of taboo languages as a whole and taboo words in each category in the Gayo Community in Bener Meriah Regency. After the data analysis was carried out, the final results of the study were found, namely all 41 words taboo, consisting of (1) taboo mentioning 15 words, (2) taboo mentioning 4 word animal names, (3) taboo names of 3 words, ( 4) taboo mentions the name of the disease 4 words, (5) taboo refers to certain words 6 words, and (5) taboos call expletives 9 words.